Use of Statins and Hip Fracture Risk: a Case-Control Study - Del Chiaro, A; Marchetti, S; Parchi, P. D; Caprili, G; Ipponi, E; Scaglione, M (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY To evaluate a possible association between hip fracture and statin use. MATERIAL AND METHODS In this case-control study we compared the use of statins between two groups of 210 patients: the first group (case group) included patients hospitalized for hip fractures while the second group (control group) included patients who did not suffer femur bone injuries. The two groups were matched for age, sex, year of hospitalization and possible confounding factors. Inside the group of cases, we also evaluated the differences in terms of fracture type, presence of previous fragility fracture and mortality between statin users and non-users. RESULTS The use of statins was most common among patients without previous fractures (OR=0.54; 95% CI=0.33-0.89; p=0.0138), especially in older patients (OR=0.40; 95% CI=0.22-0.76). We did not find any significant difference in statin intake between men and women in the control group. In the case group, those who did not use statins were more likely to undergo a medial hip fracture (28.5% vs 16.1%). Patients from case group also presented a greater mortality (27.9% vs 19.35%) and an higher percentage of previous hip fractures (20.11% vs 9.7%). However, they didn't presented a significant higher rate of fragility fractures in other sites. DISCUSSION AND CONCLUSIONS Our study suggests a reduced hip fracture risk, especially in cases aged 80 or more, a different fracture pattern (lower percentage of medial fractures) and a reduced mortality at 9 months in patients treated with HMG-CoA reductase inhibitors, confirming the previous evidences reported in literature. Key words: statin, hip fractures, fracture risk, osteoporosis.
Keywords: Hydroxymethylglutaryl-CoA Reductase Inhibitors; Female; statiny; Aged; fraktury kyčle; Bone and Bones; Hip Fractures; Osteoporosis; Humans; ženské pohlaví; Case-Control Studies; kosti a kostní tkáň; senioři; lidé; mužské pohlaví; Male; studie případů a kontrol; osteoporóza